Differences in Perceptions of Incivility Among Disciplines in Higher Education. Issue 5 (September 2019) - Wagner, Becka; Holland, Cindra; Mainous, Rosalie; Matcham, William; Li, Gengxin; Luiken, Jessica
Abstract : Background: Incivility occurs in various forms in higher education and negatively affects teaching and learning outcomes. It has not been determined if incivility is more prevalent in one discipline than another. Purpose: The purpose of this study was to compare faculty and student perceptions of incivility across disciplines at a large public university. Methods: In this descriptive comparative study, a convenience sample of 156 faculty and 421 students completed the Incivility in Higher Education–Revised survey electronically. Results: The total sample was 577. Nursing reported the highest level of perceived incivility, with all other disciplines also reporting some level of incivility. Faculty perceived more incivility than students. Conclusions: With a national awareness of incivility in nursing education, this study shows that incivility also exists in other disciplines and is a starting point for addressing its impact on higher education. Abstract : Supplemental digital content is available in the text.